Precarization on Spotify: the work of musicians mediated by streaming platforms (Orfeu, 2026)
Streaming has been the main driver of growth in the music industry since 2017, according to data from the International Federation of the Phonographic Industry (2024). This research aims to explore the relationship among the streaming platform Spotify, the precarization of work in the music industry, and the platformization of labor. To this end, semi-structured interviews were conducted with independent artists who upload tracks to the platform, complemented by bibliographic research and documentary analysis. The main findings of the study include a description and analysis of the pitching process; insights into Spotify’s management from the interviewees' perspective; an analysis of the streaming service's terms of use; and a discussion of the meanings associated with autonomous work. This research concludes that the relationship between musicians and Spotify is characterized by competitiveness and the hierarchization of artists within the streaming ecosystem, power imbalances, a lack of transparency between the platform and the artist, and insufficient compensation for music plays, factors that contribute to the precarization of work in music.